Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Please, explain me why the derivative of $$(\sin \theta)^{n-1} = (n-1)\cos\theta \cdot (\sin \theta)^{n-2}$$

Thanks so much!

share|improve this question
4  
Have you studied the chain rule? –  hardmath Oct 27 '12 at 20:58
    
$\sin^n \theta$ is a more convenient way of writing $[\sin \theta]^n$. –  BobaFret Oct 27 '12 at 21:04
    
@BobaFret: Ok thanks, I'll remember. –  calbertts Oct 27 '12 at 21:07
add comment

5 Answers 5

up vote 1 down vote accepted

It's chain rule:

first you take the derivative of $\sin^{n-1} (x)$, it becomes $(n-1)\sin^{n-2} (x)$ then you have to take the derivative of $\sin( x)$ which is $\cos (x)$ and so the answer is $(n-1)\cos (x) \sin^{n-2} (x)$

share|improve this answer
1  
Your answer is very nice!, thanks –  calbertts Oct 27 '12 at 21:14
    
"first you take the derivative of $\sin^{n-1}(x)$"...with respect to what? –  Cameron Buie Oct 29 '12 at 2:55
add comment

$\sin^{n-1}\theta$ is the composition $f\circ g$ of $f\colon x\mapsto x^{n-1}$ and $g\colon x\mapsto \sin x$. Therefore the chain rule applies: $(f\circ g)'(\theta)=g'(\theta)f'(g(\theta))$.

share|improve this answer
    
Thanks by your time, now I understand. –  calbertts Oct 27 '12 at 21:13
add comment

A combination of power rule and chain rule.

Put $u=\sin\theta$, so that $\sin^{n-1}\theta=u^{n-1}$. By power rule, $$\frac{d}{du}\left[u^{n-1}\right]=(n-1)u^{n-2}=(n-1)\sin^{n-2}\theta.$$ By chain rule, $$\frac{d}{d\theta}\left[\sin^{n-1}\theta\right]=\frac{d}{d\theta}\left[u^{n-1}\right]=\frac{d}{du}\left[u^{n-1}\right]\cdot\frac{du}{d\theta}=(n-1)\sin^{n-2}\theta\cdot\cos\theta.$$

share|improve this answer
    
Thanks by your time. –  calbertts Oct 27 '12 at 21:09
add comment

Using chain rule, we get that $$\dfrac{d ((f(x))^k)}{dx} = \dfrac{d ((f(x))^k)}{d f(x)} \dfrac{d f(x)}{dx} = k (f(x))^{k-1} \dfrac{df(x)}{dx}$$ In you case, $f(x) = \sin(x)$, $k=n-1$. Recall that the derivative of $\sin(x)$ is $\cos(x)$.

share|improve this answer
    
Thanks by your time. –  calbertts Oct 27 '12 at 21:12
add comment

You can prove it by induction and using the product rule of differentiation i.e. $(f\cdot g)'= f'\cdot g+f\cdot g'$

for $k=2$ it holds $(\sin ^{2-1}x)'= (\sin x )'= (2-1)\cos x \sin ^0 x$

assume it holds for

$k=n-1$ $$(\sin ^n x )'=(\sin x \sin ^{n-1} x)'= (\sin x)'\sin ^{n-1} x +\sin x (\sin ^{n-1} x )'$$ by induction we get $$=\cos x \sin ^{n-1} x +\sin x (n-1) \cos x \sin ^{n-2} x = n \cos x \sin ^{n-1} x$$

share|improve this answer
    
Good!, thanks so much! –  calbertts Oct 27 '12 at 21:29
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.